The Effect of Application of Diplazium Esculentum Leaf Extracts and GA3 on the Berry Quality of Grape (Vitis Vinifera L.) Cultivar of ‘Prabu Bestari’ - I Nyoman Gede Astawa; Rindang Dwiyani; Ni Nyoman Ari Mayadewi; Prila Kartika Manulang; Anak Agung Made Astiningsih (Agro Bali : Agricultural Journal, 2023)
This study investigated the effect of extract of Diplazium esculentum leaves and GA3 on the berry quality of Vitis vinifera c.v. Prabu Bestari. The objective of this research was to find out the effect of the application of D. esculentum leaf Extract and GA3 on the berry quality of grape c.v. Prabu Bestari. This study was conducted in the Vineyard at the Experimental Station of the Faculty of Agriculture, Udayana University during April to October 2021. A total of five different treatments were applied on inflorescences of grape (by dipping them), i.e. T0= control, only distilled water; T1 = 200 cc leaf extract was diluted with distilled water in to 1 L (200 cc L-1); T2=400 cc L-1; T3 = 600 cc L-1; T4= 500 ppm GA3 (as control positive). There were five treatments arranged in a randomized block design with 6 repetition.  The results showed that all treatments were not able to induce seedless, as seeds still presented inside berries, however, the number of seeds in the treatment of 500 ppm GA3 reduced significantly compared to other treatments.  Weight per seed decreased significantly at 400 cc L-1 D. esculentum extract, 600 cc L-1 D esculentum extract and 500 ppm GA3.